The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11011-016-9913-z
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-like neuroprotection of isopsoralen against spinal cord injury through estrogen receptor ERα

Abstract: Isopsoralen is a type of furocoumarin that exhibits estrogen-like activities. The aim of this study was to determine the estrogen-like neuroprotection of isopsoralen in an animal model of spinal cord injury (SCI). Results indicated that isopsoralen (intraperitoneal injection of 5 and 10 mg/kg per day for two weeks) significantly enhanced the hindlimb locomotor functions of mice with SCI, as revealed in the BMS score and angle of inclined plane tests. Morphological data showed that isopsoralen significantly att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The treatment of MC3T3-E1 cells and primary rat osteoblast cells with angelicin increased the expression of ERa protein (Ge et al, 2018;Ge et al, 2019). A similar increase in ERa by angelicin in the grey matter of ventral and dorsal horns were also reported in adult male C57BL/6 mice that had suffered spinal cord injury (Li et al, 2017a). Other than that, to determine if angelicin were only upregulating ERa and not ERb, Xin et al (2010) incubated HeLa cells with angelicin and they confirmed that angelicin only increases ERa transcription activity.…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancersupporting
confidence: 56%
“…The treatment of MC3T3-E1 cells and primary rat osteoblast cells with angelicin increased the expression of ERa protein (Ge et al, 2018;Ge et al, 2019). A similar increase in ERa by angelicin in the grey matter of ventral and dorsal horns were also reported in adult male C57BL/6 mice that had suffered spinal cord injury (Li et al, 2017a). Other than that, to determine if angelicin were only upregulating ERa and not ERb, Xin et al (2010) incubated HeLa cells with angelicin and they confirmed that angelicin only increases ERa transcription activity.…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancersupporting
confidence: 56%
“…ERα potentiates bones response to mechanical strain, and regulates trabecular bone formation and thereby trabecular bone volume in female and male mice (35,36). A recent study demonstrated that angelicin exhibits estrogen-like activity and induces the upregulation of ERα in a spinal cord injury model (17). In the present study, angelicin was associated with an increase in ERα protein levels in rat primary osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…For studies of the effects of hippocampal estrogen depletion, mice were given systemic injections of formestane (2 mg/kg, s.c.; Tocris Bioscience) daily for 7 d with the last treatment 1 d before experimental use. For behavioral experiments, mice were given intraperitoneal injections of the following drugs (or vehicle): MPP or PHTPP (0.6 mg/kg, 60 min before behavior) dissolved in saline with 5% DMSO (Labouesse et al, 2015;Li et al, 2017).…”
Section: Methodsmentioning
confidence: 99%